Effect of silica fume and solid borax waste on compressive strength of fired briquettes - Sola, Ozlem Celik; Sayin, Baris; Ozyazgan, Cemil; Bostancı, Levent (Revista de la Construcción. Journal of Construction, 2017)
It is a well-known fact that industrial solid wastes which are commonly employed in construction sector make a significant contribution in reduction of environmental pollution. In this study, solid borax waste and silica fume were used as additive materials. In the briquette compositions, 3, 5 and 10% proportions of solid borax waste and 2, 5 and 10% proportions of silica fume were used in mixtures. In order to determine material characterization, micro structure (SEM) analyses of solid borax waste and silica fume were performed besides of physical and mechanical tests. Moreover, DTG analyses were implemented to specify material’s behavior under high temperature loads. According to the test results, the values of maximum compressive strength and minimum bulk density were obtained using mixtures with proportions of 2% silica fume and 10% solid borax waste. Additionally, it was determined that the briquettes having low density and high compressive strength could be produced using aforementioned all mixtures.